Formulation and Characterization of Gliclazide Oral Dissolving Films - Kaza, Rajesh; Prasanna Raju, Y.; Nagaraju, R. (Drug Delivery Letters, 2014)
This recent research work was aimed to develop the oral dissolving films of gliclazide. Solid dispersions of gliclazide using natural polymers such as hupu gum (HG), guar gum (GG) and xanthan gum (XG) were prepared by kneading technique and the optimized solid dispersion was exploited to develop the gliclazide films. Different grades of HPMC (E5, 50 cps and K4M) were used to develop the films by adapting solvent casting method. Six formulations (FG1-FG6) of gliclazide films were prepared. The films were evaluated for their thickness, tensile strength, elongation, weight variation, folding endurance, drug content uniformity and surface pH and obtained satisfactory results. The films were assessed for their compatibility between the drug and excipients by FTIR and DSC techniques. The film formulations were subjected to disintegration, in vitro drug release and pharmacodynamic studies. From the results FG4 formulation was found as best formulation which contains HPMC K4M and gliclazide solid dispersion with guar gum at weight ratio of 1:2. The formulation had showed excellent film characteristics such as disintegration time of 64 sec and drug release was 97.30 % within 10 min. The optimized film formulation (FG4) showed excellent stability over 45 days when stored at 40°C /60% RH. The pharmacodynamic study in animal models (rats) proved that fast dissolving films of gliclazide produced a faster onset of action compared to that of conventional formulation.
Keywords: folding endurance